2015
DOI: 10.9734/ijtdh/2015/14461
|View full text |Cite
|
Sign up to set email alerts
|

Rabies Virus Neutralizing Antibodies in Unvaccinated Rabies Occupational Risk Groups in Niger State, Nigeria

Abstract: AZ and MDH designed and involved in sample collection, shipment across the Niger State to Zaria, Nigeria and some literature search. Author AG supported by other laboratorians in CDC, USA made necessary arrangements for the shipment of samples to CDC, Atlanta, USA, conducted the laboratory procedures (RFFIT), literature review and reviewing of the final draft. All authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…In this study, 29/373 (7.8%) dog butchers who had never been vaccinated with rabies vaccine, had NTA against rabies virus with a low titer (GMT5 0.25 IU/mL. This finding is similar to that of Garba et al, 18 who examined groups at risk of rabies, including dog meat consumers, butchers, owners, hunters, and veterinarians. They found that 14.8-25% of unvaccinated professional groups had NTA against rabies with titers ranging from 0.05 to 0.65 IU/mL.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, 29/373 (7.8%) dog butchers who had never been vaccinated with rabies vaccine, had NTA against rabies virus with a low titer (GMT5 0.25 IU/mL. This finding is similar to that of Garba et al, 18 who examined groups at risk of rabies, including dog meat consumers, butchers, owners, hunters, and veterinarians. They found that 14.8-25% of unvaccinated professional groups had NTA against rabies with titers ranging from 0.05 to 0.65 IU/mL.…”
Section: Discussionsupporting
confidence: 87%
“…Also, dog butchers often fail to be vaccinated or use personal protective equipment (PPE) when handling dogs [23]. Indeed, two studies reported the presence of RBV antibodies in dog butchers without a prior history of vaccination [24,82], suggestive of previous exposure and potential subclinical infection. These findings are of public health concern and highlight the need for health promotion interventions targeting dog butchers in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…The other two were never vaccinated but still had titers because they are exposure to the work of lifting live (for animal birth control, ABC) as well as dead (for disposal) animals (Dogs/Monkeys etc.) reported to the corporation and may have acquired immunity because of that as is proved in many such conditions like handling and butchering dogs in African countries like Nigeria [6] and pose serious risk to such people by such animals [7]- [9] as 22.6% of apparently healthy dogs were found to be positive for rabies virus in Nigeria [10] [11]. This poses serious risk to dog handlers of municipalities and therefore urgent need for pre exposure rabies vaccination.…”
Section: Resultsmentioning
confidence: 99%